Scaling up climate-smart dairy practices in Kenya through Nationally Appropriate Mitigation Actions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The livestock sector is responsible for 14% of all human-induced greenhouse gas emissions, making it a key sector for mitigation action. Within the dairy sector specifically, better feed production and feeding practises can bring strong mitigation and livelihood benefits, while providing increased resilience to climate change. By focusing on the mitigation benefits derived from these practices as an entry point, the dairy sector of Kenya is leveraging climate finance to promote sustainable development. A meta-analysis of various climate-smart dairy practices, industry know-how, as well as the latest Nationally Appropriate Mitigation Actions (NAMAs), was conducted to establish a repertoire of best practices.